2002
DOI: 10.1029/2002eo000411
|View full text |Cite
|
Sign up to set email alerts
|

RANGES improves satellite‐based information and land cover assessments in southwest United States

Abstract: PAGES 601-612RANGES Improves Satellite-based Information and Land Cover Assessments in Southwest United States PAGES 601,[605][606] Because of its influence on hydrology climate, and global biogeochemical cycles, land cover change may be the most significant agent of global environmental change. Land degradation results not only from land cover conversion, but also land cover function. For example, human activities in the southwest U.S.,such as grazing regimes and fire frequency, are accel erating functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(58 citation statements)
references
References 2 publications
0
51
0
Order By: Relevance
“…Due to the issue of cloud cover, a set of images was selected representing only nine months of the year 2014 (January, February, April, May, Jun, July, August, September, October). In order to improve the predictive capability for toxic metals in soils and as we assumed that vegetation cover may provide important information for soil toxic metals' spatial modeling, the following spectral indices were derived from the satellite images: BCI, biophysical composition index [43]; EVI, enhanced vegetation index [44]; LSWI, land surface water index [45]; NDVI, normalized differential vegetation index [46]; SATVI, soil-adjusted total vegetation index [47,48]; SAVI, soil-adjusted vegetation index [49]; TVI, transformed vegetation index [50]; WDVI, weighted difference vegetation index [51,52]; and tasseled cap transformation including brightness, greenness and wetness [53]. The formulas used to derive these indices are shown in Table 2.…”
Section: Remote Sensing Images and Spectral Indicesmentioning
confidence: 99%
“…Due to the issue of cloud cover, a set of images was selected representing only nine months of the year 2014 (January, February, April, May, Jun, July, August, September, October). In order to improve the predictive capability for toxic metals in soils and as we assumed that vegetation cover may provide important information for soil toxic metals' spatial modeling, the following spectral indices were derived from the satellite images: BCI, biophysical composition index [43]; EVI, enhanced vegetation index [44]; LSWI, land surface water index [45]; NDVI, normalized differential vegetation index [46]; SATVI, soil-adjusted total vegetation index [47,48]; SAVI, soil-adjusted vegetation index [49]; TVI, transformed vegetation index [50]; WDVI, weighted difference vegetation index [51,52]; and tasseled cap transformation including brightness, greenness and wetness [53]. The formulas used to derive these indices are shown in Table 2.…”
Section: Remote Sensing Images and Spectral Indicesmentioning
confidence: 99%
“…NDWI (Normalized Difference Water I) (C−NIR2)/(C + NIR2) [46] Texture GLCMh1 GLCM homogeneity sum of all directions from NIR1 and NIR2 [37] GLCMh2 [37] GLCMd1 GLCM dissimilarity sum of all directions from NIR1 and NIR2 [37] GLCMd2 [37] GLCMe1 GLCM entropy sum of all directions from NIR1 and NIR2 [37] GLCMe2 [37] The OBIA software eCognition v. 8.8 was employed for the extraction of the object-based features from both Landsat 8 and WV2 orthoimages shown in Tables 3 and 4 [37][38][39][40][41][42][43][44][45][46]. To this end, the chessboard segmentation algorithm included in eCognition was applied on a thematic layer composed of a previously digitized vector file with the 694 reference greenhouses.…”
Section: Tested Features Description Referencementioning
confidence: 99%
“…where NDSVI is the Normalized Difference Senescent Vegetation Index [21]. In addition, the widely used Normalized Difference Vegetation Index (NDVI) was included:…”
Section: Reflectance Measurementsmentioning
confidence: 99%
“…Nevertheless numerous crop residue/soil tillage indices have been reported that use various combinations of the Landsat Thematic Mapper (TM) bands [16,[18][19][20][21][22]. These indices are based on relative differences in broad band reflectance for soils and crop residues.…”
Section: Introductionmentioning
confidence: 99%